Impact of thermal annealing on graphene devices encapsulated in hexagonal boron nitride. Issue 12 (29th September 2014) - Engels, Stephan; Terrés, Bernat; Klein, Felix; Reichardt, Sven; Goldsche, Matthias; Kuhlen, Sebastian; Watanabe, Kenji; Taniguchi, Takashi; Stampfer, Christoph
<x xml:space="preserve">Abstract</x> We present a thermal annealing study on single‐layer and bilayer (BLG) graphene encapsulated in hexagonal boron nitride. The samples are characterized by electron transport and Raman spectroscopy measurements before and after each annealing step. While extracted material properties such as charge carrier mobility, overall doping, and strain are not influenced by the annealing, an initial annealing step lowers doping and strain variations and thus results in a more homogeneous sample. Additionally, the narrow 2D‐sub‐peak widths of the Raman spectrum of BLG, allow us to extract information about strain and doping values from the correlation of the 2D‐peak and the G‐peak positions.